PERANCANGAN BUKU KOMIK BUDAYA JAWA “MAHABARATHA” SEBAGAI MEDIA PENUNJANG PENDIDIKAN KARAKTER DI SEKOLAH - Rohman, Ahmad Syarifuddin (Studi Budaya Nusantara, 2019)
Character school education program aims to develop students' potentials to become a man of faith and fear of God Almighty, noble, healthy, knowledgeable, capable, creative, independent and responsible. The problem that arises is the difficulty of teachers to implement character education in learning at school. Issues that exist for this is the lack of media to support the implementation of character education in schools. Teachers find it difficult to understand and implement policies that character education program. In the study of this development is the development model used by the 4D development model Thiagarajan et al. Validation media include media expert and expertmaterial. This development is to produce media in the form of a comic book about the introduction of a puppet-based story "Mahabaratha" for high school students. Figure raised in the media include Arjuna and Krishna as the main character puppet.